Enrichment and characterization of the mRNAs of four aminoacyl-tRNA synthetases from yeast. - Sellami, M (1983)
We have partially purified the messenger RNAs for yeast arginyl-, aspartyl-, valyl-, alpha and beta subunits of phenylalanyl-tRNA synthetases in order to study their biosynthesis and ultimately, to isolate their genes. Sucrose gradient fractionation of poly U-Sepharose selected mRNAs resulted in a ten fold enrichment of the in vitro translation activity of these mRNAs. The translation products of messenger RNAs for arginyl- and valyl-tRNA synthetases have the same molecular weight as the purified enzymes; translation of aspartyl-tRNA synthetase messenger RNA yielded a 68 kD molecular weight polypeptide (while the purified cristallisable enzyme appears as a 64-66 kD doublet, which, as we showed is a proteolysis product). The translation of the mRNAs for alpha and beta phenylalanyl-tRNA synthetase gave polypeptides having the same molecular weight as those obtained from the purified enzyme, but the major translation products are slightly heavier, indicating that they may be translated as precursors. As estimated from centrifugation experiments mRNAs of arginyl-, aspartyl-, alpha and beta subunits of phenylalanyl-tRNA synthetase were 1700-2000 nucleotides long, indicating that alpha and beta are translated from two different mRNAs.